Forced Marriage and Mental Health by migrants in Germany - Kizilhan, Jan Ilhan (Archives of Community Medicine and Public Health, 2017)
Background and Objectives: The study examines the extent to which a link exists between forced marriage and the frequency of mental illness. Methods: Female migrants both in forced marriages and not in forced marriages with a Turkish background were compared in psychosomatic clinics in Germany with regard to their psychological complaints. Results: Turkish women in forced marriages suffer from mental health problems with significantly greater frequency and, on average, have attempted suicide at least four times. Conclusion: They suffer the consequences of a forced marriage for their entire lives, and they require special psychosocial counselling and both medical and therapeutic treatment which takes specific cultural and migration aspects into consideration.